Android attendance solution / Aslina Baharum … [et al.] - Baharum, Aslina; Kai Jie, Wong; Abdul Rahim, Emelia; Halamy, Suhaida; Omar, Muhammad (Division of Research and Industry Linkages, 2017)
In Universiti Malaysia Sabah, signing attendance is very inefficient. Usually, the signing of attendance starts when the lecturer gives out the attendance sheet and entering the lecture hall. This will not only distract the class, it will also cause someone to miss the attendance sheet because of the passing process is not consistent. There is also potential data loss due to human's mistake such as misplacing the attendance sheet. In order to solve these problems, this project proposes an Android-based application integrated with a web application to make the process of signing attendance more efficient.